MAKNA SIMBOLIK TRADISI MONDHOSIO DI DUSUN PANCOT, KALISORO, TAWANGMANGU, KARANGANYAR - Aprilia Ika Nur Janah (UIN Raden Mas Said Surakarta, 2020)
This article aims to explore the meaning behind the tradition of bersih desain the Kalisoro, Tawangmangu, Karanganyar, Central Java. Bersih desais indeed widely practiced in various regions in Java. However, there are unique things happening in this Tawangmangu area. apart from being a place famous for its tourist base, the people in it are indeed made up of various beliefs. This study uses a descriptive qualitative approach that describes the results of interviews and field observations. The results of this study show that the activities of bersih desa, there is a mondhosiotradition which on one side presents offerings to the spirit of the local village, but on the other hand there is an Islamicnuance that appears there. Islamic nuances are indicated by votive expressions, and other symbols such as alms and good wishes. This shows that the mondhosiotradition has existed for experienced acculturation with the times and exceeded their Javanese beliefs. This study becomes interesting to do and become one of the legacies of local wisdom as part of the rich diversity of Indonesian society.